Efektivitas Sisiometri di Zaman Sekarang - M. Fazli; Nurfarhanah Nurfarhanah; Zadrian Ardi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Siometry is a psychological measurement tool used to determine interpersonal relationships in small groups. In the digital era marked by rapid social and technological changes, the effectiveness of siometry needs to be re-examined. This study aims to evaluate the effectiveness of using siometry in identifying group dynamics, especially in the context of modern education and organizations. The method used is a literature study with a qualitative descriptive approach. The results of the study indicate that siometry remains relevant and effective in revealing social structures and individual relational preferences, especially when combined with digital technology such as interactive applications. However, some limitations arise related to bias in perception and interpretation of the results. In conclusion, siometry is still an effective tool for social mapping, with greater potential if integrated with modern technology.